The Influence of Social Support on Work-Life Balance with Job Satisfaction as a Mediatior among Employees of Pt Aseli Dagadu Djokdja - Wicaksono, Dewi; Kurniawan, Ignatius Soni; Purnamarini, Tri Ratna (Universitas Muhammadiyah Pontianak, 2026)
Employees in creative industries often struggle with work–life balance and job satisfaction due to continuous innovation demands. This study investigates the impact of social support on work–life balance, with job satisfaction as a mediator, among employees of PT Aseli Dagadu Djokdja. Survey data from eligible employees (incidental total sampling) reveal that social support significantly affects job satisfaction (β = 0.514, p < 0.001) and work–life balance (β = 0.568, p < 0.001). Although job satisfaction influences work–life balance (β = 0.251, p = 0.004), its mediating effect is not supported.